Anti-pollution mixed matrix membrane with high efficiency for removing antibiotics and preparation method thereof
Patent Information
- Application Number
- CN202410302773.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-18
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2044-03-18
AI Technical Summary
Existing membrane materials suffer from poor antifouling performance and a trade-off between permeability and selectivity when treating wastewater. They are difficult to effectively remove both large and small molecular pollutants, and the catalysts are difficult to recover and can easily cause secondary pollution.
MIL-101(Fe) material was prepared by a solvothermal method, and CS@MIL-101(Fe)-PAA/PVDF composite membrane was prepared by a non-solvent phase separation method. Combined with advanced oxidation technology, the separation of macromolecular pollutants and the removal of small molecule pollutants were achieved.
It improves the membrane's resistance to fouling and its service life, enhances the separation effect of macromolecular pollutants, and efficiently removes small molecule pollutants through advanced oxidation technology, thereby reducing the cost of industrial wastewater treatment.
Smart Images

Figure CN117959952B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of polymer membrane preparation technology, and relates to an anti-fouling mixed matrix membrane for efficient removal of antibiotics and its preparation method. Background Technology
[0002] Membrane separation technology, which has emerged in recent decades, is widely used in wastewater treatment due to its advantages such as high efficiency, low energy consumption, and no secondary pollution. However, traditional membrane materials suffer from drawbacks in wastewater treatment, including poor antifouling performance and a trade-off between permeability and selectivity. These drawbacks not only reduce separation efficiency but also significantly limit the further development and application of membrane technology. Therefore, developing new membrane materials and optimizing membrane separation processes are essential. Surface segregation technology can achieve in-situ three-dimensional modification of ultrafiltration membranes, featuring simultaneous membrane formation and modification, simple operation, and self-healing capabilities, making it a promising method for preparing antifouling membranes. However, single membrane modification methods can only enhance the membrane's antifouling ability to a certain extent and cannot completely remove pollutants. In recent years, advanced oxidation technologies have shown promising applications in water treatment, including photocatalysis, electrocatalysis, Fenton catalysis, and Fenton-like catalysis. These technologies generate highly reactive substances to oxidize pollutants through free radical or non-free radical pathways, offering advantages such as good treatment effect, fast speed, and complete removal of organic matter. Therefore, combining membrane separation technology with advanced oxidation technology to prepare antifouling membranes can solve this problem.
[0003] Metal-organic frameworks (MOFs) are a class of hybrid porous materials with infinite topological structures, formed by the bridging of metal clusters or metal ions with organic ligands in two- or three-dimensional space through repeating coordination entities. MIL-101(Fe) is a common MOF-based catalyst, possessing advantages over traditional catalysts, including large specific surface area, high porosity, open metal sites, and ease of functionalization. Furthermore, MIL-101(Fe) has unsaturated metal coordination sites, which can generate charge-separated states by exciting metal nodes, providing high-density active centers, promoting the activation of peroxymonosulfate (PMS), and enhancing photocatalytic performance, thus facilitating the degradation of organic pollutants. Jianjun Song et al. prepared a highly active and stable MIL-101(Fe) / g-C3N4 composite catalyst using a hydrothermal method. Under light irradiation, the catalyst degraded tetracycline hydrochloride (TC) using advanced oxidation techniques. Experimental results showed that the catalyst exhibited higher catalytic activity, achieving a TC degradation rate of up to 85.7%, and maintaining a TC degradation efficiency of 75% even after five cycles. It is evident that MIL-101(Fe) has broad prospects for both theoretical research and practical wastewater treatment in the field of antifouling membrane material construction.
[0004] Ruiyu Bao's research group reported the preparation of a novel PVDF / Fe-MILs in-situ polymerized membrane. A certain amount of FeCl3·6H2O was dispersed in a solution containing PVDF, PVP, and DMF and mechanically stirred for 1 h. H2BDC or NH2-H2BDC was then added to the solution to prepare a casting solution. The casting solution was cast onto a clean glass plate using a doctor blade and immersed in a water bath for phase inversion, thus preparing the novel PVDF / Fe-MILs in-situ polymerized membrane. The surface structure, chemical structure, hydrophilicity, permeate flux, retention capacity, photocatalytic activity, and self-cleaning ability of the novel membrane were investigated. The results showed that the composite membrane exhibited enhanced hydrophilicity, excellent photocatalytic performance, and excellent stability. It showed good removal efficiency for dyes such as methylene blue (90%) and antibiotics (69%) in water, and the degradation efficiency remained essentially unchanged after four cycles. However, this method uses a simple phase inversion method to prepare composite membranes, which cannot effectively control the distribution of photocatalysts within the membrane. This can easily lead to the deposition of some photocatalytic nanomaterials at the bottom of the membrane, thus hindering their catalytic effect during wastewater treatment. Fe-MILs photocatalysts tend to accumulate and aggregate within the membrane pores, exhibiting poor dispersion. This not only reduces permeate flux but also affects the membrane's separation performance and lifespan.
[0005] Ke Zhu's research group reported the preparation of a wreath-like MIL-101(Fe) / MoS2 nanosheet. A two-step hydrothermal method was used to prepare the MIL-101(Fe) / MoS2 nanosheets. First, FeCl3·6H2O, DMF, and H2BDC were hydrothermally reacted at 110℃ to generate MIL-101(Fe) material. Then, NH4[Mo(NO3)2] and CS(NH2)2 were added to a homogeneous MIL-101(Fe) solution, and a black MIL-101(Fe) / MoS2 nanosheet catalyst was generated by hydrothermal reaction at 180℃. Experimental results showed that the MIL-101(Fe) / MoS2 nanosheets accelerated the Fe... 3+ / Fe 2+ Cycling effectively promotes the activation of PMS, resulting in good removal efficiency for organic pollutants in water, and exhibits excellent stability and reusability, with a removal rate still reaching 92% after five cycles. However, this catalyst lacks a membrane carrier, and the nanosheet catalyst is difficult to recover and separate after degrading pollutants in water, easily causing secondary pollution, which limits its practical application or promotion. Secondly, this technology mainly relies on the catalytic activation of PMS to degrade organic pollutants. The catalyst is prone to agglomeration in the pollutants being degraded, leading to a reduction in the specific surface area of the catalyst, weakening the catalytic effect, and making the operation process and reaction conditions relatively complex, with high production costs.
[0006] Based on the above analysis, the invention of a composite membrane that has a good separation effect on macromolecular pollutants in water, an excellent removal effect on small molecule organic pollutants, and a longer service life, as well as its preparation method, is urgently needed in the industry. Summary of the Invention
[0007] In view of the above-mentioned shortcomings, this invention provides a structurally stable CS@MIL-101(Fe)-PAA / PVDF antifouling membrane. First, MIL-101(Fe) material is prepared by a direct mixing method, and then CS is used to functionalize the MIL-101(Fe) material. Using PVDF as the raw material, PVP as the hydrophilic agent, and DMAc as the solvent, different concentrations of positively charged blending agent CS@MIL-101(Fe) and negatively charged PAA are introduced into the casting solution and coagulation bath, respectively. The CS@MIL-101(Fe)-PAA / PVDF antifouling membrane is prepared by non-solvent-induced phase separation (NIPS), achieving the separation of macromolecular pollutants such as protein (BSA). Then, in conjunction with advanced oxidation technology, small molecule pollutants such as tetracycline hydrochloride (TC) are removed. This invention creatively synthesizes a novel membrane material with antifouling properties, providing a reference for further expanding the application scope of nanomaterials in membrane separation and developing and constructing more novel high-performance antifouling membrane materials. Furthermore, by improving the structure of the membrane material itself and the advanced oxidation mechanism, the separation efficiency and service life of the membrane can be increased, ultimately achieving the practical goal of green and environmentally friendly treatment while reducing the cost of industrial wastewater treatment.
[0008] This invention is achieved through the following technical solution:
[0009] A method for preparing a highly efficient antibiotic-removing antifouling hybrid matrix membrane, comprising:
[0010] MIL-101(Fe) material was prepared using a solvothermal method; and
[0011] CS@MIL-101(Fe)-PAA / PVDF composite membranes were prepared by a solvent-inducing phase separation method.
[0012] Furthermore, the solvothermal preparation of MIL-101(Fe) material includes the following steps:
[0013] (1) Dissolve 4.9 mmol FeCl3·6H2O and 2.48 mmol H2BDC in DMF liquid and sonicate at room temperature and pressure for 30 min to obtain precursor solution;
[0014] (2) After the precursor solution was vacuum dried and heated, it was centrifuged to obtain a solid product. The solid product was washed twice with DMF and hot ethanol, each time for 3 hours, and then centrifuged again to obtain an intermediate substance.
[0015] (3) The intermediate material is vacuum dried and then activated by heating to obtain MIL-101(Fe) material.
[0016] Further, in step (1), the mass of FeCl3·6H2O is 1.35g, the mass of H2BDC is 0.412g, and the volume of DMF liquid is 30mL.
[0017] Furthermore, the drying conditions described in step (2) are 20 hours at 110°C.
[0018] Further, the drying conditions in step (3) are 2 hours at 70°C; the activation conditions are 8 hours at 150°C.
[0019] Furthermore, the preparation of the CS@MIL-101(Fe)-PAA / PVDF composite membrane by the solvent-free phase separation method includes:
[0020] (1) Pour CS and MIL-101(Fe) materials into DMAc solvent and ultrasonically stir at room temperature and pressure for 1 hour to obtain the first solution;
[0021] (2) Dissolve PVP in the first solution and stir ultrasonically for 1 hour to obtain the second solution;
[0022] (3) Dissolve PVDF powder in the second solution, mechanically stir at high temperature and cool naturally, and degas at room temperature to obtain degassing casting solution;
[0023] (4) The defoaming casting solution was scraped into a film with a thickness of 200 μm and pre-evaporated. It was then separated in a PAA coagulation bath. The detached film was taken out and soaked in deionized water for 48 h to obtain a pretreated film.
[0024] (5) The pretreated membrane is washed with deionized water and dried to obtain CS@MIL-101(Fe)-PAA / PVDF composite membrane, which is an anti-fouling ultrafiltration membrane for high-efficiency removal of antibiotics.
[0025] Further, in step (1), the mass of CS is 0.18g, the mass of MIL-101(Fe) material is 0.36g, and the mass of DMAc solvent is 76.46g.
[0026] Furthermore, the mass of the PVP in step (2) is 4g.
[0027] Furthermore, the mass of the PVDF powder in step (3) is 19g;
[0028] The high temperature is 70°C, the mechanical stirring time is 8 hours, and the room temperature degassing time is 24 hours.
[0029] Furthermore, the pre-evaporation time in step (4) is 30 seconds.
[0030] Further, the PAA coagulation bath in step (4) is prepared by the following method:
[0031] Weigh 800 mg of PAA powder and dissolve it in 800 mL of deionized water. Stir the solution with ultrasonication for 2 hours to obtain a 0.1 wt% PAA coagulation bath.
[0032] The present invention also discloses an antifouling ultrafiltration membrane for highly efficient removal of antibiotics prepared according to any of the above preparation methods.
[0033] The beneficial effects of this invention are as follows:
[0034] This invention constructs a novel antifouling hybrid matrix membrane using the NIPS method, resulting in several superior effects, mainly as follows:
[0035] 1. The preparation method of this invention endows the membrane with excellent antifouling properties. In the field of membrane separation, improving membrane lifespan and antifouling performance is one of the most challenging problems. Traditional separation membranes, once fouled, often require repeated cleaning with large amounts of chemical cleaning agents to alleviate the problem, which not only reduces the separation efficiency but also damages the membrane structure. This invention promotes the directional migration of MIL-101(Fe)-based nanomaterials within the membrane through an electrostatically enhanced surface segregation strategy, improving the membrane surface structure and constructing a hybrid matrix membrane with both high hydrophilicity and antifouling properties. Figure 1 As shown in (a-f), after surface segregation modification, the surface roughness of the composite membrane is significantly reduced, the separation layer thickness is significantly increased, and the Fe element content in the composite membrane shows a significant upward trend. Experimental results show that ( Figure 2 (a~b) When the coagulation bath is H2O, the permeation flux of the pure PVDF membrane (MO) is 626.42 L / (m). 2 The BSA rejection rate was 44.90%, and the flux recovery rate (FRR) of the membrane was only 61% after four cycles. After adding CS@MIL-101(Fe) material, the permeate fluxes of the modified membranes (M1–M3) were 593.01, 539.31, and 429.16 L / (m³), respectively. 2The BSA rejection rates of the CS@MIL-101 (Fe) material increased to 54.73%, 65.09%, and 72.41%, respectively, and the FRR of the membrane increased to 72.00%, 73.00%, and 82.00% after four cycles. This indicates that the separation efficiency and antifouling performance of the membrane are effectively improved with the increase of CS@MIL-101 (Fe) material content. In the coagulation bath with 0.1 wt% PAA solution, the surface segregation antifouling membrane (M31) achieved a BSA rejection rate of 90.57%, and the FRR reached 95.00% after four cycles. Therefore, this modification scheme significantly enhances the antifouling ability of the membrane, providing a certain reference value for the development of novel antifouling membrane materials.
[0036] 2. This invention employs synergistic advanced oxidation technology to achieve efficient removal of small molecule pollutants such as antibiotics. Relying solely on the pore size sieving effect of membranes is insufficient for the effective separation of small molecule pollutants such as the antibiotic TC. For example, the retention rates of TC for M0 to M31 are 4.75%, 5.50%, 6.38%, 6.19%, and 10.18%, respectively. Figure 2 As shown in c), the expected results were not achieved. The introduction of advanced oxidation technology effectively improved the removal capacity of different membranes for TC. Under visible light conditions, when the dosage of PMS was 30 mg, the removal rates of TC by membranes M0 to M31 increased to 62.73%, 82.98%, 84.36%, 87.84%, and 99.25%, respectively. Figure 2 (As shown in d). When the dosage of PMS was 10 mg, 20 mg, 30 mg, and 40 mg, the removal rates of TC by M31 were 83%, 94.01%, 99.25%, and 98.25%, respectively. Figure 2 As shown in e), the membrane exhibits the best removal effect for TC when the PMS dosage is 30 mg. Combining membrane separation technology with advanced oxidation technology can not only solve the problems of difficult recovery and non-reusability of catalytic materials, the need for a carrier, reduced catalytic effect, and easy secondary pollution, but also combine the separation function of the membrane to directly use the composite membrane for the efficient removal of antibiotic pollutants. Attached Figure Description
[0037] Figure 1 (a) is a cross-sectional view of membrane M3; 1(b) is a cross-sectional view of membrane M31; 1(c) is a cross-sectional view of membrane M3; 1(d) is a cross-sectional view of membrane M31; 1(e) is a distribution diagram of iron in membrane M3; 1(f) is a distribution diagram of iron in membrane M31.
[0038] Figure 2(a) Permeation flux of the composite membrane to BSA; 2(b) Permeation flux of the composite membrane to BSA and membrane flux recovery rate after four cycles; 2(c) Retention rate of the composite membrane to BSA and TC; 2(d) Removal rate of the composite membrane coupled with PMS to TC; 2(e) Removal rate of TC by PMS at different concentrations. Detailed Implementation
[0039] The present invention will be further described below with reference to the accompanying drawings and embodiments.
[0040] Definitions of abbreviations and key terms
[0041] PVDF (polyvinylidene fluoride), FeCl3·6H2O (ferric chloride hexahydrate), CS (chitosan), H2BDC (terephthalic acid), DMF (N,N-dimethylformamide), DMAc (N,N-dimethylacetamide), PVP (polyvinylpyrrolidone), PAA (polyacrylic acid), BSA (bovine serum albumin), TC (tetracycline hydrochloride), NIPS (non-solvent phase inversion), PMS (activated persulfate).
[0042] Example
[0043] A method for preparing a highly efficient antibiotic-removing antifouling hybrid matrix membrane, comprising:
[0044] (1) Preparation of MIL-101(Fe) material by hydrothermal method:
[0045] ① At room temperature, 1.35 g (4.9 mmol) FeCl3·6H2O and 0.412 g (2.48 mmol) H2BDC were weighed and dissolved in a beaker containing 30 mL of LDM. The mixture was sonicated for 30 min at room temperature and pressure to obtain the precursor solution.
[0046] ② Pour the precursor solution into a 100mL hydrothermal reactor and heat it in a vacuum drying oven at 110℃ for 20h to obtain the intermediate substance;
[0047] ③ Centrifuge the intermediate substance to obtain an orange solid product. Wash it twice with DMF and hot ethanol, each time for 3 hours. Centrifuge again. Place the obtained product in a vacuum drying oven at 70℃ for 2 hours. Then raise the temperature to 150℃ and activate it for 8 hours to obtain MIL-101(Fe) material.
[0048] (2) CS@MIL-101(Fe)-PAA / PVDF composite membrane was prepared by a non-solvent phase separation method;
[0049] ① Accurately weigh 0.18g CS and 0.36g MIL-101(Fe), pour them into a reagent bottle containing 76.46g DMAc solvent, and sonicate for 1 hour at room temperature and pressure;
[0050] ② Accurately weigh 4g of PVP and dissolve it in the above solution, then continuously sonicate and stir for 1 hour to mix evenly;
[0051] ③ Accurately weigh 19g of PVDF powder and dissolve it in the above solution. Stir mechanically at 70℃ for 8 hours to fully dissolve it and obtain a homogeneous casting solution. Then, allow the casting solution to cool naturally and degas at room temperature for 24 hours.
[0052] ④ Weigh 800 mg of PAA powder and dissolve it in 800 mL of deionized water. Stir the mixture ultrasonically for 2 hours to disperse it evenly, so as to obtain a coagulation bath of 0.1 wt% PAA.
[0053] ⑤ Take out the completely degassed casting solution and slowly pour it onto a clean flat glass plate. Adjust the coating thickness to 200 μm and scrape out a film of uniform size and thickness. After pre-evaporating the film in air for 30 seconds, immerse it horizontally in a coagulation bath for 5 minutes to allow phase separation. After it has completely detached from the glass plate, remove the film and place it in another container filled with deionized water to soak for 48 hours.
[0054] ⑥ Finally, the membrane is removed again and washed with deionized water to remove the residual solvent on the membrane. After drying, a CS@MIL-101(Fe)-PAA / PVDF composite membrane (membrane number M31 shown in Table 1) is obtained, which is the anti-fouling ultrafiltration membrane for high-efficiency removal of antibiotics of the present invention.
[0055] Comparative Example
[0056] Pure PVDF membranes (M0) and antifouling photocatalytic membranes (M1-M3) were also obtained using the same method as described in this invention. Only the casting solution ratio and the coagulation bath were adjusted according to the conditions shown in Table 1:
[0057] Table 1
[0058]
[0059] Experimental Example 1
[0060] The permeation flux, rejection rate of protein molecules (bovine serum albumin (BSA)) and small molecule organic pollutants (tetracycline hydrochloride (TC)) of each numbered antifouling ultrafiltration membrane were tested at room temperature and pressure, and the removal rate of small molecule pollutants (TC) under light synergistic advanced oxidation technology was tested as the performance evaluation index of the membrane.
[0061] according to Figure 2 a and Figure 2As shown in b, when the coagulation bath is H2O, the permeation flux of the pure PVDF membrane (M0 membrane) is 626.42 L / (m²). 2 The BSA rejection rate was 44.90%, and the flux recovery rate (FRR) of the membrane after four cycles was only 61%. The permeate fluxes of the modified membranes (M1 to M3) after adding CS@MIL-101(Fe) material were 593.01, 539.31, and 429.16 L / (m³), respectively. 2 The BSA rejection rates increased to 54.73%, 65.09%, and 72.41% for the CS@MIL-101 (Fe) material, respectively. After four cycles, the membrane's free flow rate (FRR) increased to 72.00%, 73.00%, and 82.00%, respectively. This indicates that the separation efficiency and antifouling performance of the membrane are effectively improved with increasing CS@MIL-101 (Fe) material content. With a coagulation bath of 0.1 wt% PAA solution, the surface segregation antifouling membrane (M31 membrane) achieved a BSA rejection rate of 90.57%, and after four cycles, the membrane's FRR reached as high as 95.00%. Therefore, this modification significantly enhances the membrane's antifouling ability.
[0062] according to Figure 2 As shown in Figure c, the TC removal rates of membranes M0 to M31 were 4.75%, 5.50%, 6.38%, 6.19%, and 10.18%, respectively, which did not meet the expected results. The introduction of advanced oxidation technology effectively improved the TC removal capacity of different membranes. Under visible light conditions, when the PMS dosage was 30 mg, the TC removal rates of membranes M0 to M31 increased to 62.73%, 82.98%, 84.36%, 87.84%, and 99.25%, respectively (e.g., ...). Figure 2 (As shown in d). When the PMS dosage was 10 mg, 20 mg, 30 mg, and 40 mg, the removal rates of TC by M31 were 83%, 94.01%, 99.25%, and 98.25%, respectively (e.g., ...). Figure 2 As shown in e), the membrane exhibits the best TC removal effect when the PMS dosage is 30 mg. Combining membrane separation technology with advanced oxidation technology can not only solve the problems of difficult recovery and non-reusability of catalytic materials, the need for a support, reduced catalytic effect, and easy secondary pollution, but also leverage the separation capability of the membrane to directly remove small molecule pollutants.
[0063] In summary, this invention employs an electrostatically enhanced surface segregation strategy, using MIL-101(Fe) material for membrane modification. This not only improves the antifouling properties and lifespan of the composite membrane but also effectively enhances the membrane's separation efficiency for large molecular pollutants (such as proteins) in water. Furthermore, the combination of membrane separation technology and advanced oxidation technology achieves better removal of small molecule organic pollutants (such as antibiotics).
[0064] The above descriptions are merely some preferred embodiments of the present invention and are not intended to limit the present invention in any way. Those skilled in the art, inspired by the present invention, can make many equivalent changes and modifications without departing from the inventive concept of the present invention, and these all fall within the protection scope of the present invention. In the complete technical solution of the present invention, the following methods can still be used to prepare surface segregation synergistic advanced oxidation technology antifouling films to achieve the objectives of the present invention:
[0065] 1. The polymer material used in this invention is polyvinylidene fluoride (PVDF). If others use organic polymers such as cellulose acetate (CA), polyethersulfone (PES), or polysulfone (PSF) as casting materials, and if other steps are consistent with the technical solution of this invention, they can also prepare an anti-fouling hybrid matrix membrane with surface segregation technology and advanced oxidation technology, thus achieving the purpose of this invention.
[0066] 2. In this invention, MIL-101(Fe) is used as a heterogeneous catalyst added to the coagulation bath. If other catalytic materials such as graphitic carbon nitride (g-C3N4), other metal MOF catalysts such as MIL-101(Cr), or composite catalysts of other metal oxides (Fe3O4, TiO2) are added to the coagulation bath, the other steps are consistent with the technical solution of this invention, and a fouling-resistant hybrid matrix membrane with surface segregation technology and advanced oxidation technology will also be prepared, thus achieving the purpose of this invention.
[0067] 3. This invention uses CS to positively modify MIL-101(Fe). If others use other modifiers such as polyethyleneimine (PEI), 3-aminopropyltriethoxysilane (APTES), or polyethylene glycol (PEG) to positively modify MIL-101(Fe), the other steps are consistent with the technical solution of this invention, and an anti-fouling hybrid matrix membrane with surface segregation technology and advanced oxidation technology can also be prepared to achieve the purpose of this invention.
[0068] 4. In this invention, a PAA solution is used as the coagulation bath, and a CS@MIL-101(Fe) / PVDF surface segregation mixed matrix membrane is prepared via a phase inversion method. If other methods use negatively charged coagulation bath solutions, the other steps are the same as in this invention, and an antifouling mixed matrix membrane combining surface segregation technology and advanced oxidation technology can also be prepared, achieving the purpose of this invention.
[0069] 5. This invention uses an advanced oxidation technology with activated persulfate (PMS) to synergistically degrade organic pollutants. If other advanced oxidation technologies use activated perdisulfate (PDS) or other sulfate groups instead, they can also achieve the same removal effect and realize the purpose of this invention.
Claims
1. A method for preparing a highly efficient antibiotic-removing antifouling hybrid matrix membrane, comprising: (1) Preparation of MIL-101(Fe) material by solvothermal method: (1.1) Dissolve 4.9 mmol FeCl3·6H2O and 2.48 mmol H2BDC in DMF liquid and sonicate for 30 min to obtain precursor solution; (1.2) After the precursor solution was vacuum dried and heated, it was centrifuged to obtain a solid product. The solid product was washed twice with DMF and ethanol, each time for 3 hours. After centrifugation again, the intermediate substance was obtained. (1.3) The intermediate material is vacuum dried and then activated by heating to obtain MIL-101(Fe) material; and (2) Preparation of CS@MIL-101(Fe)-PAA / PVDF hybrid matrix membrane by solvent-free phase separation method: (2.1) Pour CS and MIL-101(Fe) materials into DMAc solvent and ultrasonically stir for 1 h to obtain the first solution; (2.2) Dissolve PVP in the first solution and stir ultrasonically for 1 hour to obtain the second solution; (2.3) Dissolve PVDF powder in the second solution, stir mechanically and cool naturally to remove bubbles, and obtain a defoamed casting solution; (2.4) The defoaming casting solution was scraped into a film with a thickness of 200 μm and pre-evaporated for 30 s. Phase separation occurred in the PAA coagulation bath. The detached film was taken out and soaked in deionized water for 48 h to obtain a pretreated film. The PAA coagulation bath was prepared by the following method: 800 mg of PAA powder was weighed and dissolved in 800 mL of deionized water and ultrasonically stirred for 2 h to obtain the PAA coagulation bath. (2.5) The pretreated membrane was washed with deionized water and dried to obtain CS@MIL-101(Fe)-PAA / PVDF mixed matrix membrane, which is a highly efficient antibiotic removal anti-fouling mixed matrix membrane.
2. The preparation method according to claim 1, wherein: In step (1.1), the mass of FeCl3·6H2O is 1.35 g, the mass of H2BDC is 0.412 g, and the volume of DMF liquid is 30 mL.
3. The preparation method according to claim 1, wherein: The vacuum drying and heating treatment conditions described in step (1.2) are 110 °C for 20 h.
4. The preparation method according to claim 1, wherein: The vacuum drying process described in step (1.3) is performed at 70 °C for 2 hours. The activation treatment conditions were: 150 °C for 8 h.
5. The preparation method according to claim 1, wherein: In step (2.1), the mass of CS is 0.18 g, the mass of MIL-101(Fe) material is 0.36 g, and the mass of DMAc solvent is 76.46 g.
6. The preparation method according to claim 1, wherein: The mass of PVP in step (2.2) is 4 g.
7. The preparation method according to claim 1, wherein: The mass of the PVDF powder in step (2.3) is 19 g; The mechanical stirring temperature was 70 ℃, the mechanical stirring time was 8 h, and the degassing time was 24 h.
8. A highly efficient antibiotic-removing antifouling hybrid matrix membrane prepared by the preparation method according to any one of claims 1 to 7.
Citation Information
Patent Citations
Flat-plate type mixed-matrix positive osmosis membrane based on metal-organic framework MIL-101(Cr) and preparation method
CN108031304A
Broadband spectral response type antibacterial composite film as well as preparation method and application thereof
CN115463563A
Surface segregation anti-pollution photocatalytic membrane and preparation method thereof
CN116371207A
Defective MOFs-based self-cleaning ultrafiltration membrane material as well as preparation method and application thereof
CN117181025A
